2016
DOI: 10.1007/s00382-016-3203-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential of microwave observations for the evaluation of rainfall and convection in a regional climate model in the frame of HyMeX and MED-CORDEX

Abstract: This study evaluates the potential of spaceborne passive microwave observations for assessing decadal simulations of precipitation from a regional climate model through a model-to-satellite approach. A simulation from the Weather and Research Forecasting (WRF) model is evaluated against 2002-2012 observations from the Advanced Microwave Sounding Unit (AMSU-B) and the Microwave Humidity Sounder (MHS) over the Mediterranean region using the radiative transfer code RTTOV (Radiative Transfer for Tiros Operational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 109 publications
(106 reference statements)
5
9
0
Order By: Relevance
“…As an illustration, Chakroun et al (2016) and Rysman et al (2016) test new satellite products for regional model evaluation using respectively lidar-based and microwavebased spatial products to evaluate the vertical structure of cloud and rainfall over the sea. Adloff et al (2017) use for the first time the new ESA-CCI product for the Mediterranean Sea level.…”
Section: New Reference Datasets For Med-cordex Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration, Chakroun et al (2016) and Rysman et al (2016) test new satellite products for regional model evaluation using respectively lidar-based and microwavebased spatial products to evaluate the vertical structure of cloud and rainfall over the sea. Adloff et al (2017) use for the first time the new ESA-CCI product for the Mediterranean Sea level.…”
Section: New Reference Datasets For Med-cordex Model Evaluationmentioning
confidence: 99%
“…More specific evaluations of the extreme precipitations are conducted by Drobinski et al (2016b) focusing on the scaling with local temperature on stations, by Khodayar et al (2016) focusing on one of the HyMeX case study in Fall 2012 and by Rysman et al (2016) using satellite-derived extreme precipitation indices over sea.…”
Section: Model Evaluationmentioning
confidence: 99%
“…For example, one technical reason why NCEP started all‐sky assimilation in non‐precipitating cloudy areas was because the precipitation forecast fields were not easily available in their system. In the context of climate monitoring, Rysman et al () have illustrated the very large biases that result from simulating precipitation‐affected microwave brightness temperatures without access to the vertical profiles of convective precipitation. Investigators wishing to simulate all‐sky radiances offline using archived ECMWF forecast fields cannot do this, because the convective fluxes are not archived (another issue is that not every model time step is stored).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wu et al, (2015) found that frozen hydrometeors are underestimated in WRF simulations by all convective parametrization schemes over central and eastern pacific region. Rysman et al, (2016) estimate the underestimation in WRF simulations by a factor of 5 using airborne radar in Mediterranean region.…”
Section: Spatial Distribution Of Observed and Simulated Tbmentioning
confidence: 98%
“…Though the overall pattern and location of convective clouds near the eye of cyclone matched closely with the observations, Tb inside the core can be found to vary with hydrometeor shapes and estimates. This may be attributed to deficiency of frozen hydrometeors at sub-grid scale in Kain-Fritsch convection scheme (Rysman et al, 2016). A study by Wu et al, (2015) found that frozen hydrometeors are underestimated in WRF simulations by all convective parametrization schemes over central and eastern pacific region.…”
Section: Spatial Distribution Of Observed and Simulated Tbmentioning
confidence: 98%